General And Special Physical Training. Physical Qualities Required By Table Tennis Players - G‘anieva M.Yu.; Yuldashaliyeva M.I.; Azimova S.R (Global Scientific Publishing, 2024)
This article presented information on the general and special physical fitness necessary for table tennis practitioners and on the importance of developing these qualities in different ways. Also, important aspects of these preparations are highlighted in the development of the level of physical fitness of table tennis players
Keywords: general and special physical training; psychological training; strength